2018
DOI: 10.1007/s10456-018-9642-5
|View full text |Cite
|
Sign up to set email alerts
|

Activin receptor-like kinase 1 is associated with immune cell infiltration and regulates CLEC14A transcription in cancer

Abstract: Cancer cells sustain their metabolic needs through nutrients and oxygen supplied by the bloodstream. The requirement for tumor angiogenesis has been therapeutically exploited in the clinical setting mainly by means of inhibition of the vascular endothelial growth factor family of ligands and receptors. Despite promising results in preclinical models, the benefits for patients proved to be limited. Inadequate efficacy similarly halted the development of agents impinging on the activity of the activin receptor-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 50 publications
(60 reference statements)
1
36
0
Order By: Relevance
“…The CEBPB gene has already been described as a vitamin D target in myeloid leukemia cells [72]. ACVRL1 is a transmembrane protein of the transforming growth factor beta superfamily, which mediates the bone morphogenetic protein (BMP) 9-and BMP10-induced signaling that orchestrates the development of blood vessels [73]. This relates to the control of monocyte to macrophage differentiation [74].…”
Section: Discussionmentioning
confidence: 99%
“…The CEBPB gene has already been described as a vitamin D target in myeloid leukemia cells [72]. ACVRL1 is a transmembrane protein of the transforming growth factor beta superfamily, which mediates the bone morphogenetic protein (BMP) 9-and BMP10-induced signaling that orchestrates the development of blood vessels [73]. This relates to the control of monocyte to macrophage differentiation [74].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of CLEC14A expression reported that it is upregulated in many solid tumours including those of the ovary, prostate, breast, liver, bladder, kidney and lung [1,2]. This may partly reflect the reduced flow rate often present within tumour vasculature [3]; however, recent studies indicate that, in cancer, CLEC14A expression may be regulated by other pathways [4]. Poor tumour growth in CLEC14A (−/−) mice compared to wild type mice confirmed that CLEC14A promotes tumour growth [5].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) accounts for 8.5% of cancer‐related deaths and effective approaches to control CRC include oxaliplatin (OXP), 5‐fluorouracil (5‐FU), and irinotecan (CPT‐11; Bocci et al, ; Chrifi et al, ). Unfortunately, a considerable proportion of CRC patients develop acquired resistance, and thus the overall survival rate of CRC patients is 12–18 months (Abukar et al, ; Botker et al, ).…”
Section: Introductionmentioning
confidence: 99%